Estrategia de branding para la diferenciación y posicionamiento del negocio de venta de frutas Carmen - Gaibor Tenemaza, Alex Ismael (2022)
A branding strategy to achieve the differentiation and positioning of the fruit business "Carmen" in front of its competition was develop as the objective of this research. To carry out the study, a non-experimental design was used, with a qualitative approach, exploratory, field and bibliographic research type, with a historical-logical method, bibliographic review techniques, direct observation and instruments such as bibliographic records and field journal. A proposal was developed, taking into account the BRIEF, BRIFING and BUSINESS CANVAS, based on the experiential branding strategy prior to the analysis of the above mentioned tools, which were used to propose a model proposal that seeks to generate a customer’s shopping experience before their arrival at the store and after the purchase or visit the sale point, in order to build a visual image of the Big Fruit business that contributes to the positioning and maintenance in the market.